Synthesis and characterization of novel aromatic-aliphatic polyamides from bis-[(4-aminobenzyl)-4-benzamide] ether - Patil, A. S.; Medhi, M.; Sadavarte, Nilakshi V.; Wadgaonkar, P. P.; Maldar, Noormahamad N. (Materials Science and Engineering B-Advanced Functional Solid-State Materials, 2010)
A novel aromatic diamine monomer containing preformed aromatic-aliphatic amide and ether linkage, bis-[(4-aminobenzyl)-4-benzamide] ether (BABE) was prepared from 2-phenylacetonitrile. BABE was characterized by FT-IR, (1)H NMR, (13)C NMR and mass spectrometry. Five new aromatic polyamides were prepared by low temperature solution polymerization from BABE and different mole proportions of isophthaloyl chloride (IPC) or terephthaloyl chloride (TPC). The resulting polymers were characterized by means of FT-IR, inherent viscosity [eta(inh)], solubility, differential scanning calorimetry [DSC], thermogravimetric analysis [TGA] and X-ray diffraction [XRD]. Polyamides were obtained in good yields and had moderate to high molecular weights as indicated by inherent viscosities in the range 0.63-1.35 dL/g in (DMAc + 4% LiCl). XRD results showed the partly crystalline nature of polymers and these polymers dissolved in aprotic polar solvents containing LiCl. The solubility of copolyamides improved due to random placement of constituent IPC and TPC during polymerization. DSC analysis of these polyamides showed glass transition temperatures in the range of 197-204 degrees C, and they showed no weight loss below 336 degrees C when analyzed by TG. These polyamides have potential applications as engineering materials. (C) 2009 Elsevier B.V. All rights reserved.
Conference on Specialty Advanced Materials and Polymers for Aerospace and Defense and Applications (SAMPADA-2008), Mat Res Soc Singapore, Singapore, SINGAPORE, JUL 03-08, 2005
Keywords: Bis-[(4-aminobenzyl)-4-benzamide] ether; ether linkage; Inherent viscosity; polyamides; thermal stability; XRD